Decision-making process in voting during the 2024 election in Indonesia (A Study in Bandung Regency) - Kartini, Dede Sri; Adinadya Putra, Mohammad Desgia; Zainudin, Arif (Frontiers in Political Science, 2025)
IntroductionThis study investigates the complex decision-making processes of voters in Indonesia’s 2024 general election, focusing on Bandung Regency. As a cornerstone of democracy, electoral outcomes are shaped by behaviors extending beyond simple rational choice. This research aims to map these behaviors to understand the quality of democratic engagement within Indonesia’s evolving political landscape.MethodsThe study employed a qualitative methodology guided by Behavioral Decision Theory (BDT). Data were collected through verbal protocol interviews, where sampled participants articulated their thoughts, emotions, and actions during their decision-making process. The transcribed verbal data were then analyzed using thematic analysis to identify patterns and classify decision-making typologies.ResultThe analysis revealed five distinct models of voter decision-making, Closed: Automatic, heuristic-based choices relying on social norms, family loyalty, or habitual party affiliation. Semi-open: A selective process where voters use filters like religious affiliation (e.g., Nahdlatul Ulama) or political party ties to limit and evaluate candidates. Open: Deliberative and comprehensive evaluation of candidate profiles, leadership qualities, and policy programs. Mixed: Voters employ different strategies (closed, semi-open, open) for different electoral levels (e.g., presidential vs. legislative) based on perceived importance and cognitive load. Coattail-driven: Voting for legislative candidates based on support for a specific presidential candidate, though this effect was not always consistent.DiscussionThe findings demonstrate that voter rationality is dynamic and context-dependent, heavily influenced by technology (e.g., digital media algorithms), socio-cultural identity, emotional trust, and political heuristics. The prevalence of closed and semi-open processes highlights vulnerabilities to disinformation and identity politics. Enhancing the quality of Indonesian democracy requires targeted political education, electoral reforms addressing informational asymmetries, and a deeper understanding of these multifaceted decision-making processes.